Household fuel use, smoking and prevalence of self-reported allergic rhinitis in university students in Palestine: a cross-sectional study - El Sharif, Nuha; Hnaihen, Lana (Frontiers in Allergy, 2024)
PurposeIn Palestine, few studies investigated the prevalence of allergies and the factors associated with their occurrence. An online survey was conducted on health complex University students in Jerusalem to determine the prevalence of allergy rhinitis (AR) and its relationship with indoor environmental exposures.MethodsThis study employed a modified online Google form of the Global Asthma Network's Adult Questionnaire. The data were reported as frequency and percentage. The chi-square test of independence was performed to investigate the association between AR diagnosis and other factors. Multivariable models were used to identify the independent risk factors for AR after adjusting for potential confounders.ResultsData was collected from a total of 819 participants. The mean age of the participants was 20 ± 2 years and 78.1% (n = 640) were females. The AR diagnostic rate was 10.3%. In addition, having asthma and eczema were found to be substantially associated with AR. Additionally, a family history of AR and other allergens were major predictors of AR. The findings revealed that utilizing animal dung for heating increased the likelihood of AR fourfold (AOR = 4.870, p-value = 0.004), whereas e-cigarette vaping increased the possibility of AR by 2.5 times. However, using natural gas for cooking was not significantly associated with AR, and participant age was only slightly associated with AR diagnosis.ConclusionsOur study found that the AR prevalence rate is low when compared to the same population in other countries. Genetics, biomass fuel consumption, and e-smoking are all significant risk factors for AR in Palestine. An awareness campaign must be developed to educate university students and the general public about the risks of smoking, indoor air pollution, respiratory disorders, and AR. Longitudinal research is required to discover whether these associations are only transient.